Genome-wide expression analysis of carboxylesterase (CXE) gene family implies GBCXE49 functional responding to alkaline stress in cotton - Cun Rui; Fanjia Peng; Yapeng Fan; Yuexin Zhang; Zhigang Zhang; Nan Xu; Hong Zhang; Jing Wang; Shengmei Li; Tao Yang; Waqar Afzal Malik; Xuke Lu; et al. (BMC Plant Biology, 2022)
Abstract Background Carboxylesterase (CXE) is a type of hydrolase with α/β sheet hydrolase activity widely found in animals, plants and microorganisms, which plays an important role in plant growth, development and resistance to stress. Results A total of 72, 74, 39, 38 CXE genes were identified in Gossypium barbadense, Gossypium hirsutum, Gossypium raimondii and Gossypium arboreum, respectively. The gene structure and expression pattern were analyzed. The GBCXE genes were divided into 6 subgroups, and the chromosome distribution of members of the family were mapped. Analysis of promoter cis-acting elements showed that most GBCXE genes contain cis-elements related to plant hormones (GA, IAA) or abiotic stress. These 6 genes we screened out were expressed in the root, stem and leaf tissues. Combined with the heat map, GBCXE49 gene was selected for subcellular locate and confirmed that the protein was expressed in the cytoplasm. Conclusions The collinearity analysis of the CXE genes of the four cotton species in this family indicated that tandem replication played an indispensable role in the evolution of the CXE gene family. The expression patterns of GBCXE gene under different stress treatments indicated that GBCXE gene may significantly participate in the response to salt and alkaline stress through different mechanisms. Through the virus-induced gene silencing technology (VIGS), it was speculated that GBCXE49 gene was involved in the response to alkaline stress in G. barbadense.